The impact of servicescape on patronage intention: Evidence from Arabic restaurants in Shah Alam / Muhammad Ashraaf Ahmad Razib - Ahmad Razib, Muhammad Ashraaf (Faculty of Business Management, 2017)
Intense competition in the business environment forces firms to look for ther best approach to attract and create patronage intention. Servicescape is a strategy used by many firms to maintain patronage intention. Good implementation of servicescape strategies will result in quality built between customers and firms. The main study of this research is to investigate the impact of servicescape on patronage intention evidence from Arabic restaurants in Shah Alam. Patronage intention being a dependent variables in this research and measured by five independent variables which is aesthetics, ambient conditions, space, seating comfort and cleanliness. A review of literature was conducted to find out the patronage intention on Arabic restaurants. The literature review confirms this relationship. This research is based on 130 respondents which collect in three Arabic restaurants area town Shah Alam which is Al Rawsha Restaurant, Sahara Tent Restaurant and Zam Zam Arabic Restaurant. Sampling method used in this study is convenience sampling. The data was analyzed using correlation coefficient and regression by using SPSS software. The findings reveal that are positive relationship between these servicescape dimensions and patronage intention. However, the result shows that ambient conditions, seating comfort and cleanliness has significant impact on patronage intention.